Cardiovascular and autonomic responses to a maximal exercise test in elite youngsters - Blasco-Lafarga, C.; Camarena, B.; Mateo-March, M. (International Journal of Sports Medicine, 2017)
To analyze cardiovascular and autonomic responses in elite youngsters, 13 male cyclists (15.43±0.51 years) performed a graded-test until voluntary exhaustion. Oxygen consumption (VO2), blood lactate (BLa), arterial oxygen saturation (SaO2), respiratory exchange ratio (RER) and rating of perceived exertion (RPE) were collected, while heart rate (HR) was registered for heart rate variability (HRV) analyses, looking for linear and nonlinear comparisons. Cyclists reached maximal exertion [RPE: 19.14±0.94; BLa: 8.92±2.51 mmol.L-1; RER: 1.04±0.03; SaO2: 92.43±2.5%] and high-level performance (4.41±0.46 W·Kg-1; 60.77±6.87 ml·Kg·min-1) once over 95% of age-predicted HRmax. VO2 and RPE increased, and RR intervals (RRi) decreased (p<0.005), whereas only the short-term scaling exponent of the Detrended Fluctuation Analysis technique (DFA1) displayed similar adaptive changes regarding intensity (p=0.011). After controlling for W·Kg-1 and RRi, DFA1100% (0.260±0.084) showed large-negative correlations with VO2max (r=-0.83; p<0.05) and RPEmax (r=-0.79; p<0.05), suggesting a strong association between the reduction in self-similar properties of the cardiac signal and the capacity to elicit at maximum in youths. Overall-HRV (lnRMSSD) and short-term variability (lnSD1) did not show any association at maximum, or significant differences regarding intensity. DFA1 might reflect ANS-CNS linkage related to cardiac respiratory controls through exercise, becoming a complementary criterion for VO2max testing in youths.